Integrated asset and liability portfolio as instrument of liquidity management in the commercial bank - Rutkauskas, Aleksandras Vytautas; Stankeviciene, Jelena (Journal of Business Economics and Management, 2006)
Liquidity, or the ability to fund increases in assets and meet obligations as they come due, is crucial to the ongoing viability of any banking organization. Therefore, managing liquidity is among the most important activities conducted by banks. Liquidity management model proposed by the authors can reduce the probability of serious problems. Indeed, the importance of liquidity transcends the individual bank, since a liquidity shortfall at a single institution can have system‐wide repercussions. For this reason, the analysis of liquidity requires bank management not only to measure the liquidity position of the bank on an ongoing basis but also to examine how funding requirements are likely to evolve under various scenarios, including adverse conditions. The authors have focused on developing a greater understanding of the way in which banks can manage their liquidity using a broad potential of integrated asset and liability portfolio. As instrument for the solution of the assessed problem the integrated total commercial bank asset and liability structure formation and management when useful occurrence of integrated structure and every outcome is followed with some guarantee to occur was chosen. An academic example is shown as an illustration for ideas analyzed. The formality and sophistication of the process used to manage liquidity depends on the size and sophistication of the bank, as well as the nature and complexity of its activities. The principles focused in the paper have broad applicability to all banks. In particular, good management information systems, analysis of net funding requirements under alternative scenarios, diversification of funding sources, and contingency planning are crucial elements of strong liquidity management at a bank of any size or scope of operations.First published online: 14 Oct 2010